2011
DOI: 10.3945/jn.111.145722
|View full text |Cite
|
Sign up to set email alerts
|

The Selenium Deficiency Disease Exudative Diathesis in Chicks Is Associated with Downregulation of Seven Common Selenoprotein Genes in Liver and Muscle

Abstract: Fast-growing broiler chicks are susceptible to Se deficiency diseases including exudative diathesis (ED). Our objective was to determine if ED could be induced by feeding a current, practical diet and if the incidence was related to selenogenome expression in liver and muscle of chicks. Four groups of day-old broiler chicks (n = 60/group) were fed a corn-soy basal diet (BD; 14 μg Se/kg; produced in the Se-deficient area of Sichuan, China and not supplemented with Se or vitamin E), the BD and all-rac-α-tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
72
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 48 publications
(49 reference statements)
12
72
1
4
Order By: Relevance
“…A number of other studies in various species reported that >75% of selenoprotein transcripts examined were downregulated significantly by selenium deficiency when just a selenium-deficient and a selenium-adequate group were compared (47)(48)(49)(50), and several reported that the majority of selenoprotein transcripts examined were downregulated significantly by selenium deficiency when 3 groups (selenium-deficient, seleniumadequate, high-selenium) were studied (51,52). In contrast, when multiple levels of selenium supplementation were used, resulting in well-defined biomarker plateaus, far fewer selenoprotein transcripts were significantly altered by selenium deficiency (20), especially in avian studies that used commercial (outbred) strains (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies in various species reported that >75% of selenoprotein transcripts examined were downregulated significantly by selenium deficiency when just a selenium-deficient and a selenium-adequate group were compared (47)(48)(49)(50), and several reported that the majority of selenoprotein transcripts examined were downregulated significantly by selenium deficiency when 3 groups (selenium-deficient, seleniumadequate, high-selenium) were studied (51,52). In contrast, when multiple levels of selenium supplementation were used, resulting in well-defined biomarker plateaus, far fewer selenoprotein transcripts were significantly altered by selenium deficiency (20), especially in avian studies that used commercial (outbred) strains (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Most selenoproteins in the kidney are intracellular enzymes with their activities relying upon a single selenocysteine residue in their main structures [28]. Although 24-25 selenoprotein genes were identified in mammals [26], only a few studies have determined collective responses of these genes to dietary Se concentrations ranging from deficiency to moderately high levels in chicken kidney [29,30]. The transcriptional response of Se is dependent selenoprotein genes.…”
Section: Introductionmentioning
confidence: 99%
“…The normal expression of selenoproteins depends on the Se level, and their expression levels decrease with Se deficiency. In the muscle and liver of broiler chickens, the expression levels of GPx1, GPx4, Sepw1, Sepn1, Sepp1, Selo, and Selk are lower due to Se deficiency (Huang et al 2011). We found that Se deficiency decreased the Txnrd1, Txnrd2, Txnrd3, Dio1, Dio2, Dio3, GPx1, GPx2, GPx3, GPx4, Sepp1, Selo, Sel-15, Seli, Sepx1, Sels, Selk, and SPS2 mRNA levels in the chicken bursa of Fabricius.…”
Section: Discussionmentioning
confidence: 64%